Perlindungan Hukum Terhadap Konsumen Pinjaman Berbasis Online oleh Otoritas Jasa Keuangan (OJK) Berdasarkan POJK Nomor 6/Pojk.07/2022 - Amatul Najla; Faisal F; Fatahillah F (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to understand and analyze the legal protection for online-based loan consumers based on POJK Number 6/POJK.07/2022 and to analyze the supervision of consumer protection for online-based loans by the Financial Services Authority (OJK). The research methodology used is a Normative Legal Research method (legal approach) and is reinforced by an Empirical Legal Research method. The research results indicate that in order to achieve consumer and public protection in the financial services sector, improvements are needed in the implementation of consumer protection by Financial Services Providers (FSPs). Legal protection for the public is divided into two aspects: Preventive Legal Protection (prevention) and Repressive Legal Protection (resolution). The role of the Financial Services Authority in technology-based lending involves the Financial Services Authority acting as a Regulator, in accordance with its functions, duties, and authorities. The role of the Financial Services Authority as a Supervisor involves overseeing the implementation of Financial Services Authority Regulations. It is recommended to the government, especially the Financial Services Authority, to conduct public awareness campaigns and educate the public about online loans, as well as to strengthen the performance of the Financial Services Authority in terms of legal protection and supervision in this banking sector.